A case of extensive hyaline deposition in facial skin caused by erythropoietic protoporphyria. (1st August 2014) - Tewari, A.; Fassihi, H.; McGibbon, D.; Robson, A.; Sarkany, R.
Summary: Although erythropoietic protoporphyria (EPP) is relatively uncommon, affecting approximately 1 in 140 000 individuals in the U.K., it is an important disease not to miss owing to the risk of acute severe liver disease in 2% of cases. EPP occurs with clinical and histological changes in the skin associated with free‐radical‐associated dermal vascular damage. This also mediates the painful photosensitivity. Severe and disfiguring hyaline deposition is extremely rare. We demonstrate that severe EPP can cause disfiguring hyaline infiltration of the skin on the hands and face, which sheds light on the mechanism of photosensitivity in EPP; it must also be differentiated from conditions such as lipoid proteinosis.